Qualidade da educação: o que dizem os pesquisadores da área e os professores do ensino fundamental - Gonzaga, Núbia Martins (2013)
This dissertation analyzes the discurses about the quality of education, historical theme of relevance to the pedagogical area that has gained prominence in Brazilian educational policies and in the media. The research conducted in the Linha de Pesquisa Educação, Trabalho e Movimentos Sociais (Research Line Education, Labor and Social Movements) was carried out to understand the conception of quality of education in our society through the analysis of documents, bibliographic study of education researchers and interviews with seven Portuguese Language and Mathematics elementary school teachers in the fifth scholar year of three schools from the Rede Municipal de Educação - RME (Municipal Education Network) of Goiânia. The research investigated the socio-historical origin of quality as a question from the productive restructuring of flexible accumulation in the working world and how the school was being transformed with this transition. The effects on education from the spatiotemporal compression were studied based on Harvey (2012) and concepts present in UNESCO documents that demonstrate a logical measurable of quality of education by the application of exams and conversion indexes, also present in Brazilian educational policies analyzed by researchers of this area. The Prova Brasil (Brazil Exam) and the Índice de Desenvolvimento da Educação Básica- IDEB (Development Index of Basic Education (IDEB) are cited as examples in the country of systemic evaluation and quality benchmarks. This research also sought to understand the issue of quality within the context of schools organized by cycles of formation, which is the model adopted across the RME. The empiric work conducted with teachers questioned the concept of quality education and proper meaning of the index IDEB within the school, since it has been widely adopted. The data showed that both researchers and teachers denounced the poor quality of public education in Brazil, citing problems with lag in student learning, little involvement of the family in monitoring the educational learning path of their children and unsatisfactory working conditions. Furthermore, the index IDEB was not considered the best reference for the analysis of quality education as a whole. The investigation revealed the need for a clarification about what is wanted by quality education, with the establishment of clear goals, strategies which solve problems and the cooperation to achieve this.